Credit risk mitigation in central bank operations and its effects on financial markets - the case of the Eurosystem - Ulrich Bindseil; Francesco Papadia (European Central Bank (ECB), 2006)
This paper reviews the role and effects of the collateral framework which central banks, and in particular the Eurosystem, use in conducting temporary monetary policy operations. First, the paper explains the design of such a framework from the perspective of risk mitigation, which is the purpose of collateralisation. The paper argues that, by means of appropriate risk mitigation measures, the residual risk on any potentially eligible asset can be equalised and brought down to the level consistent with the risk tolerance of the central bank. Once this result has been achieved, eligibility decisions should be based on an economic cost-benefit analysis. Second, the paper looks at the effects of the collateral framework on financial markets, and in particular on spreads between eligible and ineligible assets.
Keywords: 330; Kreditrisiko; Zentralbank; Geldpolitik; EU-Staaten